Fumarate hydratase deficient renal cell carcinoma: Chromosomal numerical aberration analysis of 12 cases - Pivovarcikova, Kristyna; Martinek, Petr; Grossmann, Petr; Trpkov, Kiril; Alaghehbandan, Reza; Magi-Galluzzi, Cristina; Pane Foix, Maria; Condom Mundo, Enric; Berney, Daniel; Gill, Anthony; Rychly, Boris; Michalova, Kvetoslava; et al. (Annals of diagnostic pathology, 2019)
Hereditary leiomyomatosis and renal cell carcinoma-associated renal cell carcinoma (HLRCC)/fumarate hydratase deficient renal cell carcinoma (FHRCC) is defined by molecular genetic changes (mutation/LOH in fumarate hydratase (FH) gene). We investigated chromosomal numerical aberration pattern (CNV) in FHRCC/HLRCC using array comparative genomic hybridization analysis and low pass whole genome sequencing. Genetic analysis was successfully completed in 12 tumors. Most common chromosomal aberrations detected were a complete or partial loss of chromosome 4 (5/12 cases), chromosome 15 (4/12 cases), and chromosomes 9, 13, and 14 (each in 3/12 cases), as well as a complete or partial gain of chromosome 17 (in 4/12 cases). No chromosomal losses or gains were detected in 4 cases. Copy number variation pattern in FHRCC/HLRCC appears to be highly variable and does not provide a useful diagnostic tool in identifying these cases. Immunohistochemical staining and especially molecular genetic evaluation of FH gene mutations/LOH remain the gold standard in identifying FHRCC/HLRCC.
Keywords: Chromosomal numerical aberration pattern; Carcinoma, Renal Cell; srovnávací genomová hybridizace; lidé; Middle Aged; DNA Copy Number Variations; mužské pohlaví; karcinom z renálních buněk; Comparative Genomic Hybridization; Adult; Loss of Heterozygosity; Kidney Neoplasms; ztráta heterozygozity; ženské pohlaví; Humans; Chromosome Aberrations; Fumarate hydratase deficient renal cell carcinoma; sekvenování celého genomu; lidé středního věku; chromozomální aberace; fumarasa; Whole Genome Sequencing; dospělí; Kidney; variabilita počtu kopií segmentů DNA; Female; nádory ledvin; Male; Fumarate Hydratase